Editorial - Chan, Clare Suet Ching (Malaysian Journal of Music, 2020)
The Malaysian Journal of Music, Volume 9, presents ten articles on issues in ethnomusicology, musicology, composition, music education, popular music and music technology. These issues derive from countries including Japan, Korea, The Philippines, Thailand, Indonesia, the United States and Malaysia.